INTERWENCJA „SIŁ MIĘDZYNARODOWYCH” W IRAKU W ŚWIETLE PRAWA MIĘDZYNARODOWEGO - Malinowski, Marek M. (Wydział Prawa i Administracji UAM, 2004)
Use of armed forces against territorial integrity and political independence of any state is deemed to be an act of aggression according to the contemporary international law. The UN Charter forbids on principle resorting to violence in international relations, viewing it as a basis for maintaining international peace and security. All conflicts that lead to the use of force ought to be governed by the regime arising from the Charter, which stipulates exceptions from the general prohibition. The military action taken by the United States, the United Kingdom and some other states in Iraq and the international situation arising as a result belong to one of the most sensitive political problems of the beginning of the 21-st century. Intensive debates that have taken place over the last two years, especially massive demonstrations of the intervention opponents, have concentrated mainly on political, moral and ideological issues. The legal debate was marginal and dominated by articulation of interests or convictions. The government of the Republic of Poland has firmly endorsed the US policy, which resulted in an open conflict with Poland’s European allies. Legal arguments presented by the intervention enthusiasts, including the Polish government, were extremely unconvincing and seem to have been developed ad hoc as a result of a demand for legal justification to realize political interests. The action carried out in Iraq backed by UN Security Council Resolution 1441 did not fulfill the requirements of justified military action in compliance with chapter 7 of the UN Charter, ergo: it breached the Charter. Nonetheless, the successive resolutions of the Council: 1483, 1511 and especially 1546 granted a mandate to the international forces - initially occupying forces - to exercise power until the Coalition Provisional Authority transferred power to the legal government of Iraq, and then to the stabilizing forces acting on request of the Iraqi government to stay on the territory of Iraq and act in full cooperation with its government. Despite the breach of the UN Charter, the results of the illegal intervention were in fact accepted by the international community.
INTERVENTION OF ‘INTERNATIONAL FORCES’ IN IRAQ IN THE LIGHT OF INTERNATIONAL LAW